2023
DOI: 10.1371/journal.pone.0283906
|View full text |Cite
|
Sign up to set email alerts
|

Semiochemicals produced by fungal bark beetle symbiont Endoconidiophora rufipennis and the discovery of an anti-attractant for Ips typographus

Abstract: Bark beetles vector symbiotic fungal species into their host trees during mass attacks. The symbiotic relationship with blue stain fungi of the Ascomycetes, including genera of Endoconidiophora (syn. = Ceratocystis), promotes successful establishment whereby the microbes help to overcome the host trees’ defence and degrade toxic resins. This is the first study to evaluate both the volatile emissions from an insect-associated blue stain fungus over time and the insect response in a field trapping experiment. Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…According to Fettig et al [66], various studies conducted in north-western North America found acetophenone, (E)-2-hexen-1-ol + (Z)-2-hexen-1-ol, and verbenone provided significant protection to ponderosa pines from D. brevicomis attacks. Our results were aligned with the findings of Gaylord et al [54] and Lindmark, et al [70] for I. pini in south-western United States and I. typographus in Scandinavia, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to Fettig et al [66], various studies conducted in north-western North America found acetophenone, (E)-2-hexen-1-ol + (Z)-2-hexen-1-ol, and verbenone provided significant protection to ponderosa pines from D. brevicomis attacks. Our results were aligned with the findings of Gaylord et al [54] and Lindmark, et al [70] for I. pini in south-western United States and I. typographus in Scandinavia, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…scopulorum Engelm., trees from Ips attacks [54]. Like our findings, Lindmark et al [70] also reported a reduction in bark beetle capture using an attractant-repellent approach and suggested using semiochemicals as an effective alternative to insecticides for reducing the bark beetle population.…”
Section: Discussionsupporting
confidence: 86%
“…The ScinGOBP2 ligands can elicit antennal responses in both male and female individuals, indicating that these volatile compounds released by plants might serve as potential semiochemicals for S. cinerearia. Plant volatiles such as dipentene, decanal, cis-3-hexenyl n-valerate, and geranyl acetone have been shown to act as repellents and/or attractants for some insects [34][35][36][37][38]. In the present study, different ScinGOBP2 ligands at the same concentrations elicited different behaviors in S. cinerearia.…”
Section: Discussionmentioning
confidence: 51%
“…Anti-attractant blends offer partial protection for standing trees but are ineffective for windfallen trees. Adding new anti-attractants, e.g., geranyl acetone (Lindmark et al, 2023), to the mixture may enhance tree protection effects.…”
Section: Discussionmentioning
confidence: 99%